Investigating Patterns and Aspects of Place Naming in Toba Regency: An Anthropolinguistics Approach - Nehemia Anugrah Parasian; Tasnim Lubis; Alemina Br. Perangin-angin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research investigates the naming of huta (traditional residences) in Toba Regency from an anthropolinguistic approach, aiming to describe the linguistic performance and to formulate the underlying naming patterns. The research problem emerges from the diminishing awareness among younger generations, which threatens the continuity of historical knowledge and cultural identity embedded in huta names. Using a qualitative design with an interactive model, data were collected through in-depth interviews with traditional leaders and supported by document analysis of oral narratives and archival sources. The findings reveal that a total of 92 huta names were identified, of which 82 are polymorphemic and only 10 are monomorphemic. Polymorphemic names reflect productive morphological processes such as affixation, reduplication, and compounding, and frequently encode ecological features (e.g., rivers, hills, flora, and fauna) as well as kinship relations and cultural values. Further analysis shows that naming aspects can be categorized into manifestation (39.13%), society (33.70%), and culture (27.17%). The predominance of manifestation aspects illustrates the Batak Toba people’s ecological orientation, while the presence of clan names and ancestral references highlights the strong kinship system. Cultural aspects, meanwhile, preserve collective memories of historical events, tools, and symbolic practices. These findings show that huta naming constitute a multidimensional system that integrate linguistic, ecological, social, and cultural elements, functioning both as spatial marker and as instrument of cultural preservation. This research contributes to the development of place naming research in Indonesia and underscores the need to safeguard local wisdom through documentation and cultural education.